Science of yoga : understanding the anatomy an dphysiology to perfect your practice - Swanson, Ann, ....- (London : Dorling Kindersley Ltd, 2019)
Master your yoga asanas with confidence and ease! Explore the physiology of 30 key yoga poses, in-depth and from every angle. Scientific and medical research has demystified so much of the practice and shows the benefits of yoga to every system in the body. Delve into the science behind your favourite yoga poses with this easy-to-understand, comprehensive guide. Perfect for yogis of all levels, this reference book is an in-depth look at your physiology to help you understand how yoga works, and how to practise it safely for the best results. Find out how the spine, breathing, and body position are all fundamentally linked, and see how specific muscles respond to the movements of the joints and how alterations of a pose can enhance or reduce effectiveness. Science of Yoga reveals the benefits of yoga using up-to-date knowledge. The annotated artworks show the mechanics, the angles, and how your blood flow and respiration are affected. Learn about the key muscle and joint actions, working below the surface of each pose, and safe alignments, to get the most out of your yoga workout. Maintaining a regular yoga practice can provide many physical and mental health benefits. It can help lower your blood pressure, decrease inflammation and improve your heart health and quality of life. There are 30 key yoga poses to practise, from breathing and standing poses to inversion asanas. Perfect Your Yoga Practise The full-colour anatomical illustrations of different asanas with science-based information will give you deeper understanding of yoga and how different poses affect your body. You can achieve technical excellence in your practice and optimise the benefits of yoga on your body and mind. It also makes a fantastic gift for the yogi in your life. Inside the pages of this comprehensive yoga book, you'll discover: - The physiology of 30 key yoga poses. - Different asanas from seated and standing, to inversio
Keywords: Relaxatietechnieken ; yoga